A comprehensive study of boron nitride nanotubes multiple synthesis from a single precursor - Ahmad, P.; Khandaker, Mayeen Uddin; Amin, Yusoff Mohd (Springer Verlag (Germany), 2014)
Importance of boron nitride nanotubes due to its applications in the fields of biomedical, microelectronic mechanical systems and solid state neutron detectors has greatly increased the demand for high quality and large scale synthesis of boron nitride nanotubes. The idea of using a single precursor for multiple synthesis has been utilized and boron nitride nanotubes are synthesized from fresh as well as residual material left after first and second experimental runs. For the first time, experimental results are characterized and analyzed for their size, morphology and quality of the final product. Results thus obtained are likely to be steps toward the high yield and large scale synthesis of boron nitride nanotubes.